2015
DOI: 10.18632/oncotarget.4043
|View full text |Cite
|
Sign up to set email alerts
|

YAP is a critical oncogene in human cholangiocarcinoma

Abstract: Yes-associated protein (YAP), a transcriptional co-activator, has important regulatory roles in cell signaling and is dysregulated in a number of cancers. However, the role of YAP in cholangiocarcinoma (CCA) progression remains unclear. Here, we demonstrated that YAP was overexpressed in CCA cells and human specimens. High levels of nuclear YAP (nYAP) correlated with histological differentiation, TNM stage, metastasis and poor prognosis in CCA. Silencing YAP increased tumor sensitivity to chemotherapy and inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
117
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 49 publications
8
117
2
Order By: Relevance
“…Consistent with immunohistochemical findings 151153 , CCA cell lines display high levels of nuclear (i.e., transcriptionally active) YAP, whereas in non-malignant biliary epithelial cells, YAP is mainly sequestered in the cytoplasm 154 . Forced overexpression of YAP promoted the migratory and invasive capabilities of CCA cells, in vitro , and enhanced the metastatic dissemination of intraperitoneal CCA xenografts.…”
Section: Novel Signaling Mechanisms and Trascription Factors Promotinsupporting
confidence: 83%
See 2 more Smart Citations
“…Consistent with immunohistochemical findings 151153 , CCA cell lines display high levels of nuclear (i.e., transcriptionally active) YAP, whereas in non-malignant biliary epithelial cells, YAP is mainly sequestered in the cytoplasm 154 . Forced overexpression of YAP promoted the migratory and invasive capabilities of CCA cells, in vitro , and enhanced the metastatic dissemination of intraperitoneal CCA xenografts.…”
Section: Novel Signaling Mechanisms and Trascription Factors Promotinsupporting
confidence: 83%
“…In CCA samples, high nuclear expression of YAP by neoplastic bile ducts correlated with lymph node involvement and distant metastasis, as well as with high tumor stage and grade, and was even identified as an independent prognostic factor for overall survival 151 . Consistent with immunohistochemical findings 151153 , CCA cell lines display high levels of nuclear (i.e., transcriptionally active) YAP, whereas in non-malignant biliary epithelial cells, YAP is mainly sequestered in the cytoplasm 154 .…”
Section: Novel Signaling Mechanisms and Trascription Factors Promotinmentioning
confidence: 94%
See 1 more Smart Citation
“…S10A). In contrast, Yes-associated protein (YAP) expression, which plays an important role in cholangiocarcinogenesis (27) and is reportedly activated by loss of E-cadherin (28), was significantly increased in ECC cells (Fig. S10B).…”
Section: Loss Of E-cadherin-mediated Yes-associated Protein Activationmentioning
confidence: 99%
“…Hippo, a highly conserved growth control pathway, is deregulated in several human malignancies (5-7) including human CCA (8,9). Recently, we reported that direct transfection of the biliary tree with a constitutively active mediator of the Hippo pathway, YAPS127A, along with mouse myr-Akt as a permissive factor, induces CCA in mice (10).…”
mentioning
confidence: 99%